Track analysis of agaricoid fungi of the Patagonian forests - Romano, Gonzalo Matías (2017)
Agaricoid fungi from Patagonia have been vastly studied taxonomically since 1887, and more recently ecologically. We found five generalised tracks and three nodes for a selection of nine ectomycorrhizal and nine saprophytic species. Two areas are supernodes, complex areas supported by many nodes. One of these supernodes could be a result of a lack of sampling in the Strait of Magellan area. The other could imply a biotic radiation and a differential tolerance to more arid climate conditions in the Andes mountain chain around 44.3°S, 71.5°W. Two important areas to focus future sampling of agaricoid fungi are suggested. Generalised tracks obtained match those found for weevils (Coleoptera: Curculionidae) and oribatid mites (Acari: Oribatida) distributed along the Magellanic Forest and Magellanic Moorland provinces of the Andean region. Overlap of generalised tracks among unrelated taxa supports the idea that common processes might have caused the observed patterns. The most significant and undeniable fact is that fungal species present ecological traits that can be vital for studying geological events that have marked the biotic development.